Pelaksanaan Restorative Justice dalam Penyelesaian Perkara Tindak Pidana Penganiayaan di Wilayah Hukum Kejaksaan Negeri Samarinda - Ansar Fajar Pratama; Ivan Zairani Lisi; Insan Tajali Nur (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The application of restorative justice in the Indonesian criminal justice system cannot be immediately implemented in all cases, particularly for assault crimes. This is due to limitations in implementation and inhibiting factors that arise in the field. Facts show that some law enforcement officers are still less than optimal in expediting the restorative justice process. This condition creates legal uncertainty and anxiety, especially for prosecutors handling cases. This situation also impacts the prosecutor's position, which could be questioned by superiors and supervisory committees if case resolution does not proceed according to regulations. This study uses a socio-legal research approach to examine two main issues. First, the author analyzes the implementation of restorative justice in resolving assault cases in the jurisdiction of the Samarinda District Attorney's Office. Second, the author identifies obstacles faced in implementing restorative justice in that jurisdiction. Based on the results of the study, 14 cases of assault were handled. Of these, 11 cases were successfully resolved through restorative justice mechanisms, while 3 cases were declared failed. This failure is generally influenced by the failure to meet several important requirements, including: the perpetrator being a recidivist or having previously committed a crime, a sentence exceeding five years, the absence of a peace agreement between the perpetrator and the victim, and the perpetrator's failure to fulfill their obligation to provide compensation. Therefore, it can be concluded that although restorative justice plays a crucial role in achieving a more humane and equitable resolution of cases, its implementation still faces structural and technical obstacles. Consistent efforts by law enforcement and increased understanding of the concept of restorative justice are needed for this mechanism to operate effectively, provide legal certainty, and address the community's need for justice.